Crime scene science : 20 projects and experiments about clues, crimes, criminals, and other mysterious things - Young, Karen Romano; Goldin, David (Washington, D.C. : National Geographic, 2009)
Provides instructions for experiments that explain techniques used by crime scene investigators, such as fingerprinting and handwriting analysis; and offers tips on using the workshops as science fair projects.
Includes bibliographical references and index.
6.2
5-8
5-8
Keywords: Criminal investigation -- Juvenile literature; Crime scenes -- Juvenile literature; Forensic sciences -- Juvenile literature; Science projects -- Juvenile literature; Criminal investigation; Crime scenes; Forensic sciences; Science projects; Criminal investigation; Forensic sciences; Science projects